Single-centre experience with the treatment of high-prevalence metabolic syndrome in kidney transplant patients in Bosnia and Herzegovina - Maida Dugonjić-Taletović; Denijal Tulumović; Mirna Alečković-Halilović; Mirha Pjanić; Mithad Hajder; Alma Halilčević-Terzić; Danijela Lončar; Amila Jašarević (Medicinski glasnik, 2023)
Aim: To analyse prevalence of metabolic syndrome (MS) in kidney transplant recipients at the University Clinical Centre Tuzla in Bosnia and Herzegovina (B&H), and determine effects of a modern drug therapy in achieving target metabolic control in kidney transplant patients. Methods: A single-centre prospective study that included 142 kidney transplant patients over one year follow-up period was conducted. Patient data were collected during post-transplant periodical controls every 3 months including data from medical records, clinical examinations and laboratory analyses. Results: Out of 142 kidney transplant patients, MS was verified in 85 (59.86%); after a pharmacologic treatment MS frequency was decreased to 75 (52.81%). After a one-year period during which patients were receiving therapy for MS, a decrease in the number of patients with hyperlipoproteinemia, decrease in average body mass index (BMI), glycemia and haemoglobin A1C (HbA1C) were observed. Hypertension did not improve during this period, which can be explained by transplant risk factors in the form of immunosuppressive drugs and chronic graft dysfunction. Conclusion: A significant reduction in components of the metabolic syndrome after only one year of treatment was recorded, which should be the standard care of kidney transplant patients.
Keywords: abdominal obesity; diabetes mellitus; dyslipidaemia; immunosuppressive drugs; renal graft